Study of the influence of burning on chemical properties and seed bank of Mucuri Valley (Research, Society and Development, 2019)
The objective of this study was to evaluate the effects of controlled burning on chemical properties and soil seed bank in the area of Brachiaria decumbens pasture in the mucuri valley region, by means of a scientific experiment. Soil samples reached a depth of 5 cm for the evaluation of nutrient levels after the action of the flames, and also for seed bank evaluation, were made 5 samples of 20 cm² with an average depth of 5 cm in the control soil. in the soil subjected to burning. The fire acted as a mineralizing agent of the vegetation cover, turning it into rich P, K, Ca and Mg ashes available for the remaining plants. PH levels increased in relation to oxide formation and decreased potential soil acidity. While organic matter, its values remained higher within three months after the incidence of the burn in relation to the soil destined to the control. In relation to the soil seed bank, fire may negatively affect seed viability indices and species diversity on site, or even beneficially, as a dormancy breaking agent of some plant species. In general, fire acted negatively on the percentage of seedlings, reducing about 21.62% in relation to the soil destined for the control. However, the use of fire did not alter seed bank diversity, where 7 species were found in the control soil and 8 species in the burnt soil.